Hypersonic Flow Field Reconfiguration and Drag Reduction of Blunt Body with Spikes and Sideward Jets - Guilai Han; Zonglin Jiang (International Journal of Aerospace Engineering)
Flow field reconfiguration and drag reduction have been investigated by numerically solving Navier-Stokes equations, with the 2nd order dispersion controlled dissipative scheme adopted for the convective term discretion and the 2nd order central difference scheme for viscous term. Spikes and sideward jets nearby the spike noses were set up in the front of the blunt body to reconfigure the flow field and reduce drag during hypersonic flight. The spikes and the sideward jets led to the formation of the conical shock, the reattached shock, and the circumfluence, instead of a bow shock. According to the quantitative analysis, the reconfiguration of the flow field played a dominant role in drag reduction. Basing on the locations of the reattached shock and its interaction with the conical shock, a combined parameter was proposed for a primary criterion to design the spiked bodies with sideward jets for the purpose of drag reduction.